Present status and prospects in seed production management of biennial crops in Dagestan - N.M. Velizhanov (Овощи России)
In competitive market where vegetable seeds being sold widely by home and foreign companies, it is most important to improve management in seed production branch by the right-selected places where the seed production would be realized. This challenging task is that Russian Federation has various climatic and soil zones with different level of economic state.